MINAT SISWA PADA MATA PELAJARAN IPS SEJARAH DI SMPN 09 MUKO-MUKO BENGKULU - -, MALAZI - (Pendidikan Sejarah, 2014)
This research is motivated by the lack of student interest in social studies Muko-Muko SMP SMPN 09 Muko-Muko Kecamatan Selagan Raya Bengkulu Utara. Goals to be achieved in this study is to describe the students interest in social studiesÂ  in Junior High School history Muko-Muko N 09 Bengkulu.This research included the category of field research (field research), in the presentation and processing of data including quantitative research. Subject in this study were students of class VII B Muko-Muko SMP SMPN 09 Muko-Muko Kecamatan Selagan Raya Bengkulu Utara, which amounts to 35 people. Data collection techniques used in this study is a questionnaire or questionnaires, data analysis techniques used in the this research is descriptive statistics. So it can be concluded Most of the interst of students of SMPN Negeri 09 Muko-Muko pick in social studies including high category and the factors that effect the interests of the self (Intrinsic) is the attention, pleasure, volition interesta, ideals, while the external (extrinsic) environments that include family, school, friend relationships, mass media, school facilities.